A study of the relationship between inflammation, atherosclerosis, and malnutrition in Iraqi patients on hemodialysis. - Nabeel Mahdi Mohammed Sabri (Open Journal of Physicians and Surgeons, 2023)
Background: In dialysis patients, the main cause of death is cardiovascular diseases, however, several studies documented a role for malnutrition and inflammation in the occurrence of atherosclerosis, which in turn leads to increased mortality rates among dialysis patients. Objective: To estimate the prevalence of inflammation, malnutrition, and atherosclerosis among Iraqi patients with renal failure on maintenance hemodialysis Materials and methods: This was a prospective clinical study conducted during a period of 18 months in Karbala. All patients were followed up and various information related to them (age, gender, medical condition, ...) was recorded. In addition, Doppler sonar was done for their arteries Results: 65.3% had atherosclerosis, 58.4% had malnutrition, and 43.6% had inflammation. There was a strong and direct association between atherosclerosis and inflammation, and also between atherosclerosis and low blood albumin (a measure of malnutrition). Conclusions: A high percentage of hemodialysis patients have malnutrition, inflammation, and atherosclerosis.